Sale Purchase Agreement Through Instagram: How Is The View Of The Civil Law? - Agustini, Shenti; Syarief, Elza; Agustianto, Agustianto (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Technological developments have an impact on today's business world, which is buying and selling activities carried out through Instagram.Purposes of the Research: The purpose of this study is to examine the perspective of civil law books regarding the phenomenon of buying and selling via Instagram and analyzing the best solution so that buying and selling activities via Instagram do not violate the law.Methods of the Research: The method in this study is normative juridical which uses a library approach. In answering the formulation of the problem, the juridical basis is used, namely the civil law code book and the theoretical basis, namely modern contract law theory.Results of the Research: Based on research results, buying and selling activities via Instagram are very difficult to fulfill the legal requirements of an agreement as stipulated in the civil law code. This has also led to many cases of law violations through Instagram. Therefore, it is necessary to apply the principle of good faith in the buying and selling process on Instagram.